Ultrasound evaluation of techniques for internal jugular vein puncture in children - Schettini,Sérgio Tomaz (2008)
PURPOSE: To determine by ultrasound which access and position the child must stay to obtain the best transversal section of the right Internal Jugular Vein (RIJV) allowing a safer puncture. METHODS: Three possible accesses to the RIJV, anterior, lateral and posterior, from 57 healthy children, were analyzed through ultrasound images in a sequence of positions of the head, in supine position, with or without a roll under the scapula: head centered in neutral position with and without a roll (NPP and NP); contra lateral rotation with and without a roll (CLRP and CLR), neutral position and the patient raised in 30° in Trendelenburg position (TDG). To analyze the results it was applied one statistic method, with variation analysis to the same individuals. Basic Procedures: Ultrasound evaluation in each one of the proposed positions. RESULTS: The statistical analysis of the results observed that the lateral puncture with the patient in the neutral position, in Trendelemburg without a roll, offers a bigger area in comparison to all the other options of puncture and positioning of the patient (p<0, 0001). CONCLUSION: The safer way for the puncture of RIJV in children is obtained in neutral position in Trendelemburg by lateral puncture, without a shoulder roll.